Work effectively with BIT to assist student‐veterans. Issue 3 (12th September 2018) - Hope, Joan
Abstract : When you work with student‐veterans as a disability services provider, you probably collaborate with other offices and groups on and off campus. The Veterans Affairs Administration and your institution's veteran support office are a few good resources. Your college or university's behavioral intervention team can also assist in helping student‐veterans adjust to campus life and meet the goals they set when they enrolled.